The solution in slope-intercept form for:
y + 7 = -3(x - 1) is y = -3x - 4
3x + y = -4 is y = -3x - 4
Solution:
We have been given two equations
y + 7 = -3(x - 1) and 3x + y = -4
we have been asked to simplify these equations in slope intercept form.
The slope intercept form can be written as follows:
y = mx + b
Where, m is the slope of the line and b is the y-intercept.
The y-intercept of this line is the value of y at the point where the line crosses the y axis
Now, let us write the first equation in slope intercept form as follows:
y + 7 = -3(x - 1)
y + 7 = -3x + 3
y = -3x + 3 - 7
y = -3x - 4
The slope intercept form for the first equation is y = -3x - 4
Now, let us write the second equation in slope intercept form.
This can be done as follows:
3x + y = -4
y = -3x - 4
Therefore, the slope intercept form for the second line is y = -3x - 4